PENGARUH LATIHAN PUSH UP TERHADAP KEKUATAN OTOT LENGAN DAN BAHU ATLET TENIS MEJA PUTRI PTM MANDIRI KAMPAR - Mahayun, Juli; Zainur, Zainur; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based in the results of observations that have been researchers PTM mandiri Kampar, in the women?s table tennis athlete PTM mandiri Kampar, were still lacking in arm and soulder muscles strength. This is clearly seen during practice and competitions. Where every time the women?s table tennis athlete PTM mandiri Kampar smash, the opponent player is very easy to return the smash, besides that the hand position of the athlete holding the bet is always down, not solid on the table. Thus, the purpose of this study is wheater there is an Effect Of Heavy Push Up Exercises On The Arm And Shoulder Muscle Strength Women?s Table Tennis Athlete Of PTM Mandiri Kampar. This research was conducted at PTM mandiri Kampar, Raya Pandau Road, No.2. The populations in this study were 6 independent of women?s table tennis athlete PTM mandiri Kampar and the entirepopulation was sampled as a total sampling. Based o the analysis carried out, the value of Thitung between the initial test and the final test of push up exercises on arm and shoulder muscle strength with Ttable at a significant level 0,05 indicates a Tcount of 9,90 > Ttable of 2,015. So that Ho is rejected and Ha is accepted and from the analysis it can also be concluded that there is an effect of push up exercises on the strength of the arm and shoulder muscle of the women?s table tennis athlete PTM mandiri Kampar.Key Words: Heavy Push Up, Arm and Shoulder Muscle Strength